SPEECH ACT ANALYISIS OF JACINDA ARDERN ABOUT COVID-19 - Husein Furqani Attamimy; Esti Junining; Ismatul Khasanah (UIN Alauddin Makassar, 2020)
This study attempts to analyze the illocutionary act of Jacinda Ardern speech by using Fairclough’s Critical Discourse Analysis. The data of this study is a video transcript of Jacinda Ardern’s speech on policies regarding Covid-19 which she delivered on Mar 22, 2020. The data analysis of the study is a descriptive study using Fairclough’s theory of discourse analysis. The result shows that it is known that the types of speech used in Ardern’s speech are representative and commissive illocutionary speech. From the point of view of Fairclough’s discourse analysis, Ardern’s utterances tend to use language that is straightforward, concise and easy to understand. Her utterances do not use figurative language that might be used to disguise the real language of the situation at hand. The language used by Ardern tends to be straightforward and reveal facts that occur in the field and provide sufficient explanation for the consequences that will occur in the future. However, on the other hand, she can choose good words so that people’s worries do not get bigger. She can also control and reduce public concern by giving a statement about the actions that the government will take to tackle the coronavirus.